Halal Value Chain Education: Economic Improvement Efforts in the Development of Halal Tourism Products - Masni, Harbeng; Zahar, Erlina; Hutabarat, Zuhri Saputra; Pratiwi, Heni; Tara, Firman; Sujoko, Sujoko; Andriani, Lili; Aziza, Aziza (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2024)
This research aims to improve the sharia economic sector, which is important in Indonesia's economic progress. This research is field research with a qualitative approach. This research uses two types of data sources: primary and secondary. Data collection techniques were carried out using observation, interviews with people, and documentation. The research results show that the halal value chain in the development of halal tourism products in Kampoeng Radja in Jambi City still needs improvement, such as tourism assets that are not yet sharia-based, especially culinary delights that do not yet have a halal certificate